Democracy, good governance and development in Nigeria: A focus on Munya local government area, Niger state (Singaporean Journal of Business Economics and Management, 2023)
This study examined democracy, good govemance and development in Nigeria, with a focus on Munya Local Government Area of Niger State from 2015-2023. The study also examined the effort of political leaders in improving the standard of living of the people and also assessed the effect of elected officials in providing basic social amenities to the people. The study adopted the Social contract theory. The study adopted survey research method; data were collected from the primary and secondary sources, a total number of two hundred (200) respondents formed the sample size from the study population of one hundred and three thousand, six hundred and fifty-one (103,651), through the use of questionnaire and other printed materials. The study discovered that Democracy has enhanced good governance and development for the people of Munya Local Government. The dividends of democracy have been extended to the communities of Munya Local Government Area to some extent. Social amenities like potable water, roads, primary health care centres, schools and others essential services for the citizens. The study recommends that elected political office holders should consolidate on the effort made so far by the provision of more physical infrastructures like roads, bridges, potable water and public transport to remote villages that are yet to feel the dividends of democracy. Workshops and seminars for political leaders should be organized to re-orient the elected political leaders at the Local Government level to preach the importance of transparency and accountability. Democratic administrations should manifest the spirit of accountability, responsibility and responsiveness to ensure good governance in Nigeria. The issue of rural electrification should be taken serious, this will lead to the improvement of the quality of lives of the citizens, this will also lead to improvement of economic activities in the rural areas